Impact of the COVID-19 pandemic on the mental health of people - Agarwal, Mehak; Ravi, Prithvi; Ramesh, Chitra A.; Neslin, Judson J. (International Journal Of Community Medicine And Public Health, 2021)
Background: We conducted this survey to determine the impact of covid-19 on the mental health of people during the pandemic and period of lockdown. We evaluated certain factors such as sleep changes, anxiety, mood swings, irritability, inability to concentrate, smoking and alcohol consumption changes. Methods: A cross-sectional study was conducted. We conducted an online questionnaire and circulated it via various social media platforms to record and evaluate responses of people. SPSS 16 version software and Microsoft excel sheet were used. Results: According to the results, people suffered from negative symptoms such as stress, fear, changes in smoking habits, changes in alcohol consumption, mood swings, inability to concentrate, sleep disturbances. Most people also started new coping mechanisms to help their psychological symptoms. Conclusions: An association between mental health and the outbreak of a pandemic was noticed. People experiencing these should get help and practice relaxation methods to prevent progression of their symptoms.